KORELASI KEGIATAN LITERASI FIKIH DENGAN PRESTASI BELAJAR SISWA SMP NEGERI 3 BANJARBARU KALIMANTAN SELATAN - Mahdia; Khalilurrahman, Khalilurrahman; Farid, Miftah (Dirasa Islamiyya: Journal of Islamic Studies, 2025)
This study aims to determine the relationship between fiqh literacy and students' academic achievement in the subject of fiqh among seventh-grade students at SMP Negeri 3 Banjarbaru, South Kalimantan. The research employed a quantitative approach using a correlational method. The instruments used included a questionnaire to measure students' level of fiqh literacy and a written test to assess their academic achievement in Islamic Religious Education, specifically in fiqh material. The sample consisted of 22 students selected through proportionate stratified random sampling from a population of 210 students. Descriptive analysis showed that both fiqh literacy and academic achievement were generally in the moderate category. The Pearson Product Moment correlation test yielded a correlation coefficient of 0.489 with a t-count of 2.51, which is greater than the t-table value of 1.725 at a 5% significance level. This indicates a positive and significant relationship between fiqh literacy and students' academic achievement. The findings suggest that improving fiqh literacy can contribute to enhancing students’ learning outcomes in fiqh. Therefore, fiqh literacy should be systematically developed in the learning process through contextual approaches and the provision of relevant learning resources.